The Effect of Pre-emptive Dexketoprofen Administration on Postoperative Pain Management in Patients with Ultrasound Guided Interscalene Block in Arthroscopic Shoulder Surgery. Issue 1 (2nd January 2021) - Demir, U.; Ince, I.; Aksoy, M.; Dostbil, A.; Arı, M. A.; Sulak, M. M.; Kose, M.; Tanios, M.; Ozmen, O.
Abstract: Background: Postoperative pain is an important problem for patients undergoing shoulder surgery. Our study investigated analgesic efficacy, duration of analgesia, postoperative analgesic use and patient satisfaction with the use of preemptive intravenous dexketoprofen for interscalene block in addition to general anesthesia in arthroscopic shoulder surgery. Methods: 60 patients, scheduled for arthroscopic shoulder surgery were randomized (30 patients each) into either: - control group (Group1) or dexketoprofen group (Group 2). Patients were followed for 48 hours to compare both groups for; post-operative pain scores, effectiveness of postoperative analgesia, duration of analgesia, and analgesia consumption. Duration of postoperative sensory block of the shoulder joint was defined as time to onset of pain at the incision site. Duration of postoperative motor block of the shoulder joint was defined as time to onset of first shoulder movement. Results: While no significant difference was determined for motor block time, sensory block time was significantly longer in the dexketoprofen group ( p  < 0.05).VAS scores were significantly lower at all times in the dexketoprofen group ( p  < 0.05).Total PCA fentanyl consumption was 274.16 ± 314.89 (μg) in the dexketoprofen group, and 490.00 ± 408.98 (μg) in the control group, the difference was statistically significant ( p  < 0.05). No significant difference was observed between the groups' demographic and hemodynamic data. Conclusion: Pre-emptive IV dexketoprofen may be a good option for arthroscopic shoulder surgery and provides effective analgesia.